Contextualising Late-Nineteenth-Century Feminism: Problems and Comparisons - Allen, Judith (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1990)
AbstractHistories of feminism since the 1970s have generally observed national and regional boundaries. In view of the international character of women's movements in western countries since the last quarter of the nineteenth century, the neglect of comparative approaches has been unfortunate. The outcome is parochialism and inwardness, as feminist historians evaluate feminists of the past according to current preoccupations, in a cycle of identification and repudiation. An Anglo-American hegemony in the field is identified as is the consequent and pervasive “Northern Hemispherism” it ordains (notwithstanding an almost invariable omission of Canadian feminist experience). Advantages of comparative, international approaches to the history of feminism are not confined to the virtues of representativeness and comprehensiveness. Rather, major causal and chronological schema generalised from Anglo-American experience stand to beproblematised and revised in more useful directions. Most significantly, comparative studies of feminism permit due recognition of the fact that feminism emerged relatively contiguously across western countries in response to relatively common international characteristics of transformations in sexual patternings and sexual cultures.